An Intelligent Approach to Prioritize Logistics Requirements in Food Industry - Zeki AyaÄŸ (International Journal of Supply Chain Management, 2014)
The aim of this study is to analyze dairy food industry and to determine the priorities of important logistics requirements (LR) based on customer requirements as a part of a supply management system. For product or service development, quality function deployment (QFD) is a useful approach to maximize customer satisfaction. The determination of the priorities of the LR is an important issue during QFD process for product or service design. For this reason, in this work, an integrated approach integrating fuzzy logic and QFD methods is proposed to identify and prioritize the LR in dairy food industry for the improvement of customer satisfaction. In addition, a case study in Turkish dairy food industry is given to illustrate the proposed approach for potential readers.